Pemanfaatan Digital Marketing Guna Meningkatkan Daya Saing Produk Usaha Mikro Pasca Pandemi Covid-19 Di Desa Tarai Bangun, Kampar, Riau - Herispon, Herispon; Anuar, Saiful; Iskandar, Iskandar (Indra Institute Research & Publication, 2023)
The 1st edition of PKM Efficiency Digital Marketing activities was carried out in October 2020, and the 2nd Edition of PKM Utilization of Digital Marketing activities was carried out in February 2023, with the target still being home, micro and small businesses in Tarai Bangun Village, Tambang, Kampar, who continue to struggle, and reach to be able to increase the competitiveness of products post-pandemic covid 19 by utilizing developments in internet technology within the frame of digital marketing (digital marketing). The fact has spoken that digital marketing is a must to choose, if you want to expand your marketing area and keep your business going. The real benefit of digital marketing is the opportunity for penetration and wider market reach. So digital marketing is very possible to be done by home, micro and small businesses, especially in Tarai Bangun Village, Tambang, Kampar, Riau